Dekonstruksi Gender dalam kitab Dawâirul Khaufi (Qirâah fî Khitâbil Mar’ah) Karya Nasr Hamid Abu Zayd - Aris Baidowi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
Women as melancholy beings are always in a position of authority so that the men awakened sectarian discourse-rasialistik and put women in a comparative relationship with the absoluteness of men, so necessary to the understanding of gender deconstruction effort itself in order to find the understanding of equality and partnership in the realm of culture rather than biological between males and females.